Thermally rearranged mixed matrix membranes for CO2 separation: An aging study. (June 2017) - Brunetti, Adele; Cersosimo, Maurizio; Kim, Ju Sung; Dong, Guangxi; Fontananova, Enrica; Lee, Young Moo; Drioli, Enrico; Barbieri, Giuseppe
Highlights: Separation properties of a pure TR and a TR + CNTs mixed matrix membranes. Aging behavior of a pure TR and a TR + CNTs mixed matrix membranes. No significant difference observed in aging behavior of TR + CNT membrane with respect to pure TR membrane. TR + CNTs mixed matrix membrane more permeable and selective than pure TR membrane. Abstract: In this work, the aging behavior of a thermally rearranged polybenzoxazole-co-imide (TR-PBOI) mixed matrix membrane loaded with 0.5 wt.% of oxidized multi-wall carbon nanotubes (MWCNT) was evaluated and then compared to a pure TR polymeric membrane prepared from the same precursor. To the best of authors knowledge, this is the first report of a mixed matrix membrane being prepared through the dispersion of MWCNTs within a thermally rearranged polymer matrix for CO2 separation. Microporous structures were created in both membranes when thermally rearranged at 375 °C, facilitating fast mass transfer ideal for membrane gas separation. The TR mixed matrix membrane with oxidized CNTs demonstrated improved separation properties with regard to both permeability and selectivity compared to the pure TR polymeric membrane due to a greater degree of thermal rearrangement (11.3%) than what was exhibited by the TR membrane (6.7%). Moreover, the high CO2 solubility typical of TR polymers coupled with diffusivity enhancements improved the CO2 /N2 selectivity. The addition of oxidized CNTs to the TR-PBOI polymer did not significantly influence the aging behavior of the mixed matrix membrane. Both pure TR-PBOI and mixed matrix membranes exhibited an increase in CO2 selectivity due to physical aging. The improved separation properties in conjunction with an unchanged membrane stability over time suggested that the addition of CNTs to pure TR membranes could be an excellent approach toward improving the performance of thermally rearranged membranes applied toward gas separation.